Pengaruh Total Assets Turn Over Terhadap Return On Assets Pada KSP Kopdit Pintu Air - Emilianus Eo Kutu Goo (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
Assets are wealth owned by a company. Therefore, good asset management is very necessary so that the results obtained by the company each period will be maximized. This research aims to determine the effect of Total Assets Turn Over on Return On Assets at KSP Kopdit Pintu Air. The type of research used in this research is quantitative descriptive research. The population of this research is KSP Kopdit Pintu Air while the sample used in this research is the financial report of KSP Kopdit Pintu Air from 2016 - 2020. The data collection method in this research was carried out by literature study and documentation. The data analysis technique used is simple linear regression analysis. Meanwhile, research data processing uses the help of the IBM SPSS Statistics 23 application. Based on the results of data processing and analysis that has been carried out, the results show that Total Asset Turn Over (TATO) has a significant influence on Return On Assets (ROA).